Experimental evaluation of elemental behavior during LA-ICP-MS: influences of plasma conditions and limits of plasma robustness. Issue 1 (20th October 2015) - Fietzke, J.; Frische, M.
Abstract : Hot plasma conditions stabilize elemental fractionation and provide matrix-tolerant operating conditions for LA-ICP-MS. Abstract : Matrix effects are one of the frequently observed and discussed issues challenging the accuracy of LA-ICP-MS results. The specific role of the ICP as a source of elemental fractionation seems not fully understood. We report the results of an experiment using six internationally available reference materials (five silicates, one carbonate) measured under 11 different plasma conditions. The thermal/energetic state of the plasma was estimated based on the ratio of 38 Ar + and 40 Ar2 + ions. We show that element specific behavior (volatile vs. refractory) dominates at cool but vanishes under hot plasma conditions. For robust (hot) plasma conditions matrix-tolerance seems to be achieved. Additionally we address the problem of matrix-load with respect to the plasma conditions. We've estimated practical limits for the amount of matrix which can be introduced into the ICP without significantly changing the plasma conditions.